2020
DOI: 10.3390/ma13020459
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Mechanical Behavior of Ultra-High Strength Low-Carbon Steel

Abstract: The low-carbon steel (~0.12 wt%) with complete martensite structure, obtained by quenching, was cold rolled to get the high-strength steel sheets. Then, the mechanical properties of the sheets were measured at different angles to the rolling direction, and the microstructural evolution of low-carbon martensite with cold rolling reduction was observed. The results show that the hardness and the strength gradually increase with increasing rolling reduction, while the elongation and impact toughness obviously dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…It is should be noted that Ni 3 Mo is rod-shaped, where the length direction of the rod and matrix is in the <111> direction [ 2 ]. The close-packed surface and direction of δ-Ni 3 Mo and η-Ni 3 Nb phases are parallel to the matrix, with the existence of the coherent or semicoherent relation between δ-Ni 3 Mo/η-Ni 3 Nb and matrix, thus the strength is remarkably improved [ 1 , 2 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is should be noted that Ni 3 Mo is rod-shaped, where the length direction of the rod and matrix is in the <111> direction [ 2 ]. The close-packed surface and direction of δ-Ni 3 Mo and η-Ni 3 Nb phases are parallel to the matrix, with the existence of the coherent or semicoherent relation between δ-Ni 3 Mo/η-Ni 3 Nb and matrix, thus the strength is remarkably improved [ 1 , 2 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen in Table 7 , it can be concluded that the cooling ability of the steel core is insufficient when quenching with oil, which results in lower hardness at the central core without meeting the engineering requirements for the intended application, and the hardness difference between the surface and center is about 27 HV. The tempered hardness of the steel core can reach the standard requirement when the PAG polymer medium is used for quenching and tempering; however, the hardness difference between the surface and center is still large, due to the precipitation of carbide during the tempering process [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the experimental tests (see Figure 5), the considered steel exhibits an anisotropic behaviour which is demonstrated by the variation of the mechanical properties with the in-plane direction. 31,[50][51][52] It is noticed that the hardening curves corresponding to the directions 00°, 30°a nd 45°from the rolling direction had extremely similar mechanical properties up to 20.8% in strain. In addition, the values of yield strength and maximum tensile strength were close.…”
Section: Macro-tensile Behaviourmentioning
confidence: 98%
“…Respectively, the complex properties are required for mechanical parameters of materials used for fabrication of welding elements of a frame construction. The following properties can be mentioned here: high strength (600-1100 N/mm 2 ) with reservation of sufficient level of tough and ductile parameters at low temperatures (KCV -60 t 50 J/sm 2 ) as well as weldability (C eq d 0.53) [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%